Analisis Terhadap Pelanggaran Pelayanan Purna Jual dalam Industri Otomotif (LEGAL DIALOGICA, 2025)
This study aims to identify and analyze various forms of after-sales service violations that frequently occur in the automotive industry from the perspective of Law No. 8 of 1999. Additionally, it seeks to examine and analyze the legal protection available to consumers who become victims of these violations under the same law. This research employs a normative legal research method, which involves examining legal theories, comparative law, structure or composition, and general explanations. The findings indicate that common after-sales service violations in the automotive industry such as failure to fulfill service promises, lack of transparency in information, warranty claim rejections, and the sale of counterfeit spare parts contravene Law No. 8 of 1999 on Consumer Protection. These violations cause both material and immaterial harm to consumers and undermine the trust that is crucial to the relationship between consumers and manufacturers. Legal protection for consumers affected by after-sales service violations in the automotive industry is comprehensively regulated under Law No. 8 of 1999. Consumers have the right to receive services as agreed and to claim compensation in the event of a violation. The study recommends that automotive companies are expected to improve the quality of after-sales service by fulfilling the service promises that have been given, ensuring transparency of information to consumers, not rejecting warranty claims submitted by consumers, and not providing fake spare parts, and it is expected that business actors in the automotive industry need to increase their commitment to the promises given and improve the service system.AbstrakPenelitian ini bertujuan untuk mengetahui dan menganalisis berbagai bentuk pelanggaran pelayanan purna jual yang sering terjadi dalam industri otomotif tinjau dari undang-undang No. 8 Tahun 1999 serta mengetahui dan menganalisis perlindungan hukum bagi konsumen yang menjadi korban pelanggaran pelayanan purna jual yang terjadi dalam industri otomotif berdasarkan undang-undang No. 8 Tahun 1999. Penelitian ini menggunakan metode penelitian normatif, yaitu penelitian yang melibatkan pengkajian terhadap aspek teori hukum, perbandingan hukum, struktur atau komposisi, penjelasan umum. Hasil penelitian ini menunjukkan bentuk pelanggaran pelayanan purna jual yang terjadi dalam industri otomotif seperti, ketidaksesuaian janji layanan, informasi yang tidak transparan, penolakan klaim garansi, hingga penjualan suku cadang palsu, serta perlindungan hukum bagi konsumen yang menjadi korban pelanggaran pelayanan purna jual yang terjadi dalam industri otomotif berdasarkan Undang-Undang No. 8 Tahun 1999 telah diatur secara komprehensif. Konsumen memiliki hak untuk memperoleh pelayanan sesuai dengan perjanjian, serta mendapatkan ganti rugi jika terjadi pelanggaran. Rekomendasi penelitian ini adalah diharapkan kepada perusahaan otomotif harus meningkatkan kualitas pelayanan purna jual dengan harus menepati kesesuaian janji layanan yang telah diberikan, harus memastikan informasi transaparansi kepada konsumen, tidak menolak klaim garansi yang diajukan oleh konsumen, dan tidak memberikan suku cadang yang palsu serta diharapkan kepada pelaku usaha di industri otomotif perlu meningkatkan komitmen terhadap janji yang diberikan dan memperbaiki sistem pelayanan.